Vitamin E in dermatology - Mohammad Abid Keen; Iffat Hassan (Wolters Kluwer Medknow Publications, 2016)
Vitamin E is an important fat-soluble antioxidant and has been in use for more than 50 years in dermatology. It is an important ingredient in many cosmetic products. It protects the skin from various deleterious effects due to solar radiation by acting as a free-radical scavenger. Experimental studies suggest that vitamin E has antitumorigenic and photoprotective properties. There is a paucity of controlled clinical studies providing a rationale for well-defined dosages and clinical indications of vitamin E usage in dermatological practice. The aim of this article is to review the cosmetic as well as clinical implications of vitamin E in dermatology.